2013
DOI: 10.1111/ijfs.12136
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterisation of selected physicochemical and functional properties of β‐chitosans from squid pen

Abstract: Summary Squid pen β‐chitosans prepared under various deacetylation conditions (30%, 35%, 40% and/or 45% NaOH for 15, 30 and/or 60 min) were characterised. β‐Chitosans (deacetylated with 35–45% NaOH for 15–60 min) had 87.1–96.2% degree of deacetylation (DD), 93.5–96.7% solubility and 120.5–654.9 mPa s viscosity. Treatment with 30% NaOH for 15–60 min yielded inadequately deacetylated β‐chitosans (DD = 51.9–80.2%). Two chitosans prepared under 35% NaOH for 15 min and 45% NaOH for 30 min (designated as 35%–15 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 34 publications
3
5
1
Order By: Relevance
“…The obtained degree of deacetaylation is comparable to the values reported previously for gladius of squid [6,36]. According to various literatures, the β-chitin from gladius has weaker intermolecular hydrogen bonds, which reinforces the susceptibility of β-chitin to deacetylation reaction and resulted in high degree of deacetylation to from β-chitosan [5,6,8].…”
Section: Accepted Manuscriptsupporting
confidence: 85%
See 1 more Smart Citation
“…The obtained degree of deacetaylation is comparable to the values reported previously for gladius of squid [6,36]. According to various literatures, the β-chitin from gladius has weaker intermolecular hydrogen bonds, which reinforces the susceptibility of β-chitin to deacetylation reaction and resulted in high degree of deacetylation to from β-chitosan [5,6,8].…”
Section: Accepted Manuscriptsupporting
confidence: 85%
“…Approximately, 0.078 g of β-chitin was obtained from a gladius and the amount of chitin obtained in this study was comparable with the reported result [5,8,30]. Further, the β-chitin was converted into chitosan by deacetylation procedure which was followed by ball milling to form ultra fine white powder [6].…”
Section: Characterization Of Gcspssupporting
confidence: 81%
“…The DD% was calculated from FTIR and found to be 94 ± 1.25% for chitosan synthesized from U. duvauceli which is comparatively higher than Std.CS (~85%). The DD% was higher than the result reported on chitosan isolated from the gladius of Sepioteuthis lessoniana (87.93%) [ 34 ] and comparable with gladius of Todarodes pacificus (96.2%) [ 35 ], since the DD% values may increase with increase in NaOH concentration and deacetylation time and also depend upon the source.…”
Section: Resultscontrasting
confidence: 50%
“…The molecular weight determined was found to be 109.35 kDa for CSNA synthesized from gladius of U. duvauceli . This low molecular weight may be due to the source of chitosan and also varies with other parameters such as intermolecular hydrogen bonding, dissolved oxygen concentration, chitin concentration, particle size, reaction time, concentration of alkali, and high temperature [ 35 ]. Additionally, the ash content and moisture content for CSNA analyzed were 0.3 ± 0.05% and 0.62 ± 0.15% comparable to Std.CS (0.57% ash and 0.93% moisture content).…”
Section: Resultsmentioning
confidence: 99%
“…However, β‐chitin exhibits higher swelling properties, higher reactivity and better solubility properties in a variety of solvents than α‐chitin (Tolaimate et al ., ). β‐chitin has a more open mobile allomorph of parallel sheets held by weak intrasheet hydrogen bonding compared with the more compact antiparallel sheets of α‐chitin held by strong intermolecular hydrogen bonding (Rudrapatnam et al ., ; Abdou et al ., ; Youn et al ., ,b). Different physicochemical properties of α and β forms of chitosan may cause differences in functionality with respect to edible films and coatings.…”
Section: Introductionmentioning
confidence: 99%